2015
DOI: 10.4154/gc.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Fluid inclusion study of the Boccassuolo VMS-related stockwork deposit (Northern-Apennine ophiolites, Italy)

Abstract: Several Cyprus-type volcanogenic massive sulphide (VMS) deposits occur in the Jurassic ophiolitic series of the Northern Apennines. Stratabound, stratiform and stockwork deposits were formed in the western limb of the Neotethys (Ligurian Ocean) and are observed today in basalt, gabbro and serpentinised peridotite host rocks. The studied stockwork deposit at Boccassuolo occurs in basalt and basalt breccia. Detailed petrography, fluid inclusion study, Raman spectroscopy analyses and chlorite thermometry calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…The formation temperature of chlorite from the various stockwork, stratiform and stratabound deposits vary between 50-360 • C [37] pointing to various conditions during the hydrothermal process. These data are in good agreement with the preliminary fluid inclusion data for Boccassuolo (minimum formation temperature of quartz between 70-360 • C [38]).…”
Section: 11 165supporting
confidence: 90%
See 2 more Smart Citations
“…The formation temperature of chlorite from the various stockwork, stratiform and stratabound deposits vary between 50-360 • C [37] pointing to various conditions during the hydrothermal process. These data are in good agreement with the preliminary fluid inclusion data for Boccassuolo (minimum formation temperature of quartz between 70-360 • C [38]).…”
Section: 11 165supporting
confidence: 90%
“…: methane content was not possible to check due to the small size of inclusions or strong luminescence of calcite. *: data including the previous preliminary results of [38].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As previous studies have shown, abiotic methane is associated with various petrogenetic processes (e.g. Sachan et al, 2007, Normand 2010, Miura et al, 2011, Arai et al, 2012, Blamey et al, 2012, Kiss et al, 2015, especially secondary/alteration processes (e.g. Abrajano et al, 1988, Etiope et al, 2011, 2013a, 2013b, Boschetti et al, 2013, Szponar et al, 2013, Etiope et al, 2018.…”
Section: Research Questionmentioning
confidence: 90%
“…Most of the researches, suggest that the gas measured during pulverisation of the host lithologies should derive from Aluid inclusions (e.g. Sachan et al, 2007, Normand 2010, Miura et al, 2011, Arai et al, 2012, Blamey et al, 2012, Kiss et al, 2015, but only few mention that methane can occur within secondary pores or micro-fractures (e.g. Konnikov et al 2000, Okland et al, 2014, Etiope et al, 2018.…”
Section: Research Questionmentioning
confidence: 99%